Inequalities in health: living conditions and infant mortality in Northeastern Brazil - Renata Alves da Silva Carvalho; Victor Santana Santos; Cláudia Moura de Melo; Ricardo Queiroz Gurgel; Cristiane Costa da Cunha Oliveira (Universidade de São Paulo, 2015)
OBJECTIVE To analyze the variation of infant mortality as per condition of life in the urban setting. METHODS Ecological study performed with data regarding registered deaths of children under the age of one who resided in Aracaju, SE, Northeastern Brazil, from 2001 to 2010. Infant mortality inequalities were assessed based on the spatial distribution of the Living Conditions Index for each neighborhood, classified into four strata. The average mortality rates of 2001-2005 and 2006-2010 were compared using the Student's t-test. RESULTS Average infant mortality rates decreased from 25.3 during 2001-2005 to 17.7 deaths per 1,000 live births in 2006-2010. Despite the decrease in the rates in all the strata during that decade, inequality of infant mortality risks increased in neighborhoods with worse living conditions compared with that in areas with better living conditions. CONCLUSIONS Infant mortality rates in Aracaju showed a decline, but with important differences among neighborhoods. The assessment based on a living condition perspective can explain the differences in the risks of infant mortality rates in urban areas, highlighting health inequalities in infant mortality as a multidimensional issue.